PENCEMARAN DAN PERUSAKAN LINGKUNGAN DALAM PERSPEKTIF HUKUM ISLAM - Abdul Manan (Jurnal Hukum dan Peradilan, 2015)
Regulations governing the environment in Indonesia are many and scattered in various regulations. But it seems that these regulations stand alone, no activity and effectiveness. How to environmental management are not planned and are not integrated in a harmonious and integral cause destruction and environmental pollution. Islamic law has principles that must form the basis and starting point of the activity of the social forces in order to ensure an orderly life, balance, and harmony so there is no pollution and environmental destruction that causes loss of balance and harmony of life in this world. Among these principles, namely equality, balance, benefit, mutual cooperation and justice. Through the implementation of these principles is expected to rule on the environment that has been set it can run properly.Keywords : Environmental Pollution and Destruction, Environment,Islamic law